Implementation of Mathematics Learning through OFPISA Model in Vocational High School of Banten Province - Moh. Munir; Tb. Abin Syamsudin; Hanafiah Hanafiah; R. Supyan Sauri (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2021)
This study aimed to analyze the implementation of the OFPISA learning model in the mathematics learning of vocational high school students. The method used in this study is a combination method. Two schools were used as research samples with a focus on learning the OFPISA model. The research data use triangulation techniques, namely by observation, interviews, and documentation. The test is used to analyze whether or not there is an increase in students' mathematics learning outcomes after implementing OFPISA learning. The results showed that the OFPISA model in mathematics learning for Vocational High School students could empirically improve students' creative thinking skills, increase students' enthusiasm and motivation to learn so that their learning outcomes also increased drastically, were able to find goals, facts, problems, ideas, solutions, and student admissions.